Pengaruh Penambahan Mobilisasi Saraf Medianus Setelah Diberikan Ultrasound Therapy Pada Penurunan Nilai Nyeri Carpal Tunnel Syndrome - MUJAHADAH, RUHANA FITHROTUL; , Wahyuni, SSt.FT.M.Kes; , Dwi Rosella K, S.St FT., M.Fis; , Agus Widodo, S.Fis, M.Kes (2017)
ABSTRACT Background: Carpal tunnel syndrome occurs due dpat excessive movement in the joints can lead to carpal synovial joints increases and tapping the median nerve in the carpal tunnel so that it appears one of the various complaints of pain. To reduce the pain of carpal tunnel syndrome can be given additional mobilization of the median nerve after ultrasound therapy which have been commonly used in physiotherapy services in many hospitals. Objective: To determine the effect of the median nerve mobilization after ultrasound therapy to decrease the value of the pain of carpal tunnel syndrome. Methods: This research uses quasi experimental approach, research design pre and post test two groups design. The first group of elderly given ultrasound therapy and the second group was given the mobilization of the median nerve. The number of samples in this study of 12 samples, sample taker technique by purposive sampling technique that uses existing population criteria of inclusion and exclusion. Results: In the study the effect of test used Wilcoxon test and Mann Whitney test different influences. Wilcoxon test results on the median nerve mobilization group after the addition of ultrasound therapy asymp values obtained. Sig (2-tailed) = 0.026 indicates the value of p <0.05 there is the influence of pain using the VAS value reduction in carpal tunnel syndrome. From the results of Mann Whitney test result Sig (2-tailed) = 0.183 (Asymp. Sig (2-tailed)> 0.05), which means there is no significant difference in both groups, in the sense that both have effects in lowering pain Carpal Tunnel Syndrome. Conclusion: There is the effect of adding the median nerve mobilization after ultrasound therapy to decrease the value of the pain of carpal tunnel syndrome. Keywords: Carpal tunnel syndrome, the median nerve mobilization, ultrasound therapy.